Barley Seed Aging: Genetics behind the Dry Elevated Pressure of Oxygen Aging and Moist Controlled Deterioration - Nagel, Manuela; Kodde, Jan; Pistrick, Sibylle; Mascher, Martin; Börner, Andreas; Groot, Steven P. C. (Frontiers in Plant Science, 2016)
Experimental seed ageing approaches intend to mimic seed deterioration processes to achieve a storage interval reduction. Common methods apply higher seed moisture levels and temperatures. In contrast, the “elevated partial pressure of oxygen” (EPPO) approach treats dry seed stored at ambient temperatures with high oxygen pressure. To analyse the genetic background of seed longevity and the effects of seed ageing under dry conditions, the EPPO approach was applied to the progeny of the Oregon Wolfe Barley (OWB) mapping population. In comparison to a non-treated control and a control high-pressure nitrogen treatment, EPPO stored seeds showed typical symptoms of ageing with a significant reduction of normal seedlings, slower germination, and less total germination. Thereby, the parent Dom (“OWB-D”), carrying dominant alleles, is more sensitive to ageing in comparison to the population mean and in most cases to the parent Rec (“OWB-R”), carrying recessive alleles. Quantitative trait locus (QTL) analyses using 2,832 markers revealed 65 QTLs, including two major loci for seed vigor on 2H and 7H. QTLs for EPPO tolerance were detected on 3H, 4H, and 5H. An applied controlled deterioration (CD) treatment (aged at higher moisture level and temperature) revealed a tolerance QTL on 5H, indicating that the mechanism of seed deterioration differs in part between EPPO or CD conditions.